Job - Estes, Daniel J., 1953-; Strauss, Mark L., 1959-; Walton, John H., 1952-; Rosset, Rosalie de. (Grand Rapids, Michigan : Baker Books, 2013)
"The Teach the Text Commentary Series gives pastors the best of biblical scholarship and presents the information needed to move seamlessly from the meaning of the text to its effective communication. By keeping the discussion in each carefully selected preaching unit to six pages of focused commentary, the volumes allow pastors to quickly grasp the most important information. Each unit of the commentary includes the big idea and key themes of the passage; sections dedicated to understanding, teaching, and illustrating the text; and full-color illustrations, maps, and photos.The Book of Job presents a challenge to the modern preacher and teacher, as it communicates its message in a way that is unfamiliar to most contemporary believers. But the issues it addresses--suffering, our response to it, and how God works in the world--are nevertheless relevant to the church in our day. Job teaches the surpassing sovereignty, freedom, and wisdom of God and emphasizes that even though the answers to our questions may remain hidden from us, God can be trusted. In this commentary, Daniel J. Estes provides carefully organized guidance for interpreting, teaching, and illustrating the important truths found in Job" -- Publisher description.
Introduction to Job -- Job 1. Adversity of a righteous man -- Job 2. Turning up the pressure -- Job 3. Job shatters the silence -- Job 4. How Eliphaz explains Job's adversity -- Job 5. Eliphaz thinks he knows the answer -- Job 6. Job's frustration with his friends -- Job 7. Job's complaint to God -- Job 8. Bildad has the answer (he thinks!) -- Job 9. Job considers a legal dispute with God -- Job 10. What Job wants to tell God -- Job 11. Zophar rejects Job's complaints -- Job 12. Job presents evidence against the retribution principle -- Job 13. Job turns to speak to God -- Job 14. Job tries to hope, but ends up in despair -- Job 15. Eliphaz turns up his criticism of Job -- Job 16. Job feels under attack by God -- Job 17. Job finds no hope in life or in death -- Job 18. Bildad again beats the retribution drum -- Job 19. Job's hope against hope -- Job 20. Zophar's final words for Job -- Job 21. Job destroys the friend's' major argument -- Job 22. Eliphaz condemns and counsels Job -- Job 23. Job feels both confidence and terror -- Job 24. Job asks why God allows sin to continue unpunished -- Job 25. Bildad's final attempt to answer Job -- Job 26. Job hears the whispers of God's works -- Job 27. Job speaks in place of Zophar -- Job 28. But where can wisdom be found? -- Job 29. Job recalls the good old days -- Job 30. From the heights of honor to the depths of humiliation -- Job 31. Job's final oath of innocence -- Job 32. Elihu makes his appearance -- Job 33. Elihu urges Job to listen -- Job 34. Elihu argues that God always acts justly -- Job 35. Elihu describes God as too distant and detached to listen to Job -- Job 36. Elihu points to the corrective benefit of suffering -- Job 37. Elihu finishes with a flourish -- Job 38. Yahweh speaks as the master teacher -- Job 39. Yahweh asks Job about animals -- Job 40. Yahweh directs Job's attention to Behemoth -- Job 41. Yahweh points Job to Leviathan -- Job 42. Job comes to a good end.
Includes bibliographical references (p. 263-266) and index.
Keywords: Bible. -- Commentaries